PELUANG DAN TANTANGAN METAVERSE SEBAGAI MEDIA PEMBELAJARAN SEJARAH: SEBUAH KAJIAN LITERATUR SISTEMATIS - Alim, Muhammad Rofiul (Universitas Negeri Malang, 2023)
Abstract: The metaverse technology was massively developed in the last decade. The utilization and development of the metaverse in the field of education is considered in line with the concept of society 5.0 and 21st century competencies. Innovation makes the learning process interactive by cultivating critical thinking, communication, creative thinking, and collaboration. The development of the metaverse in the field of education is an effort to present the concept of student center learning. This research method uses a literature review by collecting scientific studies, analyzing, and comparing the use and utilization of the metaverse in education. Data search procedures, data analysis, topic determination, literature review and conclusions related to the opportunities and challenges of the metaverse as a medium for learning history. Data analysis used a literature review with descriptive qualitative. The keywords in the literature search are